2012
DOI: 10.1111/j.1443-1661.2012.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the diagnostic accuracy of endoscopic ultrasonography‐guided fine‐needle aspiration (EUS‐FNA) for upper gastrointestinal submucosal or extraluminal solid mass lesions

Abstract: Overall, 25 and 22 gauge needles have a similar diagnostic accuracy. Our results suggest that 3.0 or more needle passes and combined cytologic-histologic analysis enhance the diagnostic accuracy of EUS-FNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 19 publications
3
44
0
Order By: Relevance
“…This technique obtains more adequate specimens than does biopsy with upper gastrointestinal endoscopy. Rong et al [5] reported that the diagnostic accuracy of EUS-FNAB for submucosal tumors was 85.2 % [5]. However, as in our case, EUS-FNAB does not always allow for a definitive pathological diagnosis.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This technique obtains more adequate specimens than does biopsy with upper gastrointestinal endoscopy. Rong et al [5] reported that the diagnostic accuracy of EUS-FNAB for submucosal tumors was 85.2 % [5]. However, as in our case, EUS-FNAB does not always allow for a definitive pathological diagnosis.…”
Section: Discussionmentioning
confidence: 52%
“…The most common histological type is leiomyoma; the incidence of schwannoma among benign tumors is low [15]. Esophageal schwannomas are difficult to definitively diagnose by biopsy because they are located in the submucosal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…EUS-FNA for gastric infiltrative tumors can be used to acquire cytology findings, but for large tissue specimens for histopathology analysis, with the disadvantages of difficult operations, long time and high expenses, the positive finding rate is still undesirable[14-16]. Al-Haddad et al[17] reported that the sensitivity, specificity and accuracy rates of EUS-FNA in the diagnosis of lymphoma were 80%-87%, 92%-93%, and 83%-89%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Needle diameter has not been definitively shown to significantly impact the diagnostic accuracy of EUS-FNA for subepithelial lesions [32,33], but 25-gauge needles may more easily puncture small, mobile lesions, as well as those within or adjacent to the duodenum when the scope tip may be acutely angulated.…”
Section: Endoscopic Ultrasound-guided Fine Needle Aspirationmentioning
confidence: 99%